Rational emotive behavior therapy for psychological well-being in adolescents with cerebral visual impairment in Saudi Arabia - Al-Bulayhi, Abdulrahman Ahmed; Alsamani, Omar Abdullah; Alsenani, Abdulrahim Ajyan; Alsawalem, Ibraheem Mohamed; Aljohani, Mansour Mosleh (Jurnal Cakrawala Pendidikan, 2025)
Adolescents with Cerebral Visual Impairment (CVI) face heightened risks to psychological well-being due to social barriers, reduced independence, and negative self-perception. This study investigated the efficacy of Rational Emotive Behavior Therapy (REBT) in enhancing psychological well-being among this population in Saudi Arabia. A quasi-experimental design with pre-test, post-test, and follow-up assessments was employed. Thirty adolescents (aged 16–18; 15 males, 15 females) with CVI and documented well-being deficits from Al Noor Institute for the Blind, Buraidah, were purposively sampled. Participants were divided into experimental (REBT intervention) and control groups (n = 15 each). The intervention comprised 27 REBT sessions delivered thrice weekly, targeting cognitive restructuring, emotional regulation, and behavioral skills (e.g., relaxation, assertiveness). Psychological well-being was measured using a researcher-adapted version of Ryff’s Psychological Well-Being Scales (PWB). Mann-Whitney U and Wilcoxon signed-rank tests analyzed between-group and within-group differences, respectively. Post-test results revealed statistically significant improvements (p < .001) across all PWB dimensions (self-acceptance, positive relations, autonomy, environmental mastery, purpose in life, personal growth) for the experimental group versus controls, with large effect sizes (r = 1.0). Within-group analysis confirmed significant pre-post gains (p = .001) in all dimensions. Follow-up assessments (vs. post-test) showed no significant decline (p > .05) in well-being scores, indicating sustained intervention effects. The REBT program effectively enhanced psychological well-being in adolescents with CVI, with benefits persisting post-intervention. Findings support REBT’s applicability in mitigating cognitive and emotional challenges specific to visual impairment. Integration of REBT into support frameworks for visually impaired adolescents in educational and therapeutic settings is recommended. Future research should validate these outcomes in larger cohorts and explore long-term impacts on academic and social functioning.